Late toxicities among laryngopharyngeal cancers patients treated with different schedules of concurrent chemoradiation at a rural tertiary cancer care center - Muttath, Geetha; Vinin, N.V.; Shringarpure, Kalpita; Jones, Joneetha; Balasubramanian, Satheesan; Thavarool, Sajithbabu; Ajaykumar, Shilpa (South Asian Journal of Cancer, 2019)
Background: Concurrent chemoradiation is the treatment of choice for laryngeal-pharyngeal cancers. Apart from survival organ preservation remains major aims of the treatment. Advanced radiation techniques like VMAT have shown to reduce morbidity. The purpose of our study is to assess the late toxicities in patients treated with concurrent chemoradiation and its association with dose to organs at risk. Aims: Assessment of late toxicities following concurrent chemoradiation in patients with laryngopharyngeal cancers. Materials and Methods: Retrospective study at a tertiary cancer centre on patients with laryngeal and pharyngeal cancers treated with concurrent chemoradiation with VMAT upto a total dose of 69.3 -70 Gy in 33-35 fractions and concurrent chemotherapy with Cisplatin was done. Severe late toxicities and its association with demographic and clinical parameters and dose to OAR were studied. Data was analysed using EpiData analysis v2.2.2.182. Results: Of the 93 patients studied majority were males above 55 years. Oropharynx was the commonest site (58%) with T3 and N2 in majority. Late dysphagia and odynophagia was seen in 18(21%) and 23(27%) patients respectively. 16 (17%) had tube dependence and nine (9.6%) had aspiration pneumonia. D60, V50 and V60 along with site , node positivity and weight loss were found to be significantly associated with severe late toxicity. Conclusion: Oropharyngeal cancers, node positivity and weight loss were found to have significant grade III and above toxicities including tube dependency. Dose to larynx showed association with severe late toxicities, though dose to constrictors could not.
Keywords: Chemoradiation; cisplatin; toxicities; tube dependency